2022
DOI: 10.1136/bjsports-2021-105115
|View full text |Cite
|
Sign up to set email alerts
|

Greater proportion of patients report an acceptable symptom state after ACL reconstruction compared with non-surgical treatment: a 10-year follow-up from the Swedish National Knee Ligament Registry

Abstract: ObjectivesTo compare the proportion of patients with anterior cruciate ligament (ACL) injury reporting an acceptable symptom state, between non-surgical and surgical treatment during a 10-year follow-up.MethodsData were extracted from the Swedish National Knee Ligament Registry. Exceeding the Patient Acceptable Symptom State (PASS) for the Knee injury and Osteoarthritis Outcome Score (KOOS) was the primary outcome. The PASS and KOOS4 (aggregated KOOS without the activities of daily living (ADL) subscale) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Early reconstruction after ACL injury entails superior patient-reported outcome compared with both rehabilitations alone and later ACL reconstruction. 5 6 These findings are inconclusive, since there are studies reporting no differences between patients treated with rehabilitation alone or reconstruction in patient-reported outcomes in the long term (10–20 years) after ACL injury. 19 20 On the other hand, patients treated with ACL reconstruction can report persistent symptoms and dissatisfaction with treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early reconstruction after ACL injury entails superior patient-reported outcome compared with both rehabilitations alone and later ACL reconstruction. 5 6 These findings are inconclusive, since there are studies reporting no differences between patients treated with rehabilitation alone or reconstruction in patient-reported outcomes in the long term (10–20 years) after ACL injury. 19 20 On the other hand, patients treated with ACL reconstruction can report persistent symptoms and dissatisfaction with treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent cohort studies from the Scandinavian registers indicate that patients treated with rehabilitation alone generally report poorer knee function and achieve acceptable knee function to a lesser extent 1, 2, 5 and 10 years after the ACL injury, compared with patients treated with ACL reconstruction and subsequent rehabilitation. [4][5][6] Only three randomised controlled trials (RCTs) have analysed the differences in self-reported knee function between the treatment options. [7][8][9] The RCTs did not report any clinically relevant differences between the two treatment options concerning self-reported knee function, level of sport or the prevalence of subsequent osteoarthritis (OA) 2-5 years after baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, data from Kaiser Permanente's ACLR registry was recently used to identify differences in revision risk with respect to the timing of ACL-R [36] and concomitant meniscus surgery [37]. Importantly, data collection from non-operatively treated patients with ACL injury enables the comparison of outcomes following operative and non-operative treatment approaches [38,39].…”
Section: Comparative Studiesmentioning
confidence: 99%
“…During the past decades, ACL registries have generally provided an increased understanding of the associations between different patient characteristics and patient-reported outcomes as well as the risk of sustaining a second ACL injury. Also, the ACL registries, such as the Scandinavian ACL registries, have contributed to increased knowledge of outcomes following ACL injury, allowing improved understanding of the association between different treatment options and PROMs [3][4][5][6]. However, the evidence on how to treat patients that have sustained an ACL injury is still insufficient in terms of timing of surgery, graft type, and treatment type, showing the importance of further studies and continuous development of national ACL registries.…”
Section: Introductionmentioning
confidence: 99%
“…Another paper focusing on patient symptoms comes from Gothenburg (Sweden) . 3 There have been a number of randomized trials in arthroscopic knee surgery recently, including in anterior cruciate ligament (ACL) reconstruction, that do not resoundingly support surgery as the best option. Most of these reports are relatively small numbers of patients and rely on patient-reported outcome measures, usually at two or five years.…”
Section: Acceptable Symptom State After Anterior Cruciate Ligament Re...mentioning
confidence: 99%